Makna simbolik Prosesi Minggung dalam Adat Pernikahan Masyarakat Ulu Ogan - Novitasari, Dian; Rahmawati, Umi; Oktaria, Sari (JURNAL DINAMIKA, 2024)
ndonesia is an archipelagic country that is rich in cultural, ethnic, ethnic and racial diversity, customs, values , andculture regulate several aspects of life such as social relations, society, rituals, and myths that are believed by thecommunity. The formulation of the problem in this writing is how the meaning of the Minggung procession (offerings toancestors at a wedding) in the wedding customs of the Gunung Tiga Village community is analyzed using symbolicinteractionism, which is usually carried out 2 days before the marriage contract by the Ulu Ogan community withofferings, candles, incense, roses, and prayers for the ancestors. The Minggung Procession in the Wedding Customs ofthe Ulu Ogan community is analyzed using Symbolic Interactionism Theory to see the meaning and agreement of Mind,Self, and Society. This type of research is qualitative, with in-depth interview methods. This research paradigm isconstructivist. The research results found that the meaning of Minggung agreed upon by the Ulu Ogan community isbased on self, mind, and society, the meaning of Minggung is respect for ancestors which is a form of ritualcommunication. This meaning is obtained from the thoughts of the people who consider this a tradition which is amessage from their ancestors that must be preserved.Keywords : interactionisme symbolic, Ogan’s culture, Minggung